Growth and Entrepreneurship: An Empirial Assessment - Zoltán J. Ács; David B. Audretsch; Pontus Braunerhjelm; Bo Carlsson (Max Planck Institute of Economics, 2005)
This paper suggests that the spillover of knowledge may not occur automatically as has typically been assumed in models of endogenous growth. Rather, a mechanism is required that serves as a conduit for the spillover and commercialization of knowledge from the source creating it to the firm actually commercializing the new ideas. In this paper, entrepreneurship is identified as one such mechanism facilitating the spillover of knowledge. Using a panel of entrepreneurship data for 18 countries, empirical evidence is found that in addition to measures of R&D and human capital, entrepreneurial activity also serves to promote economic growth.
Keywords: 330; Entrepreneurship; Growth; Humankapital; Wissenstransfer; Unternehmen; Unternehmer; Wirtschaftswachstum; Industriestaaten